BAKEBOX Enterprise/ Khaireen Aizamyra Khairil Anwar... [et al.] - Khairil Anwar, Khaireen Aizamyra; Munif Zarirruddin Fikri, Mawaddah; Mohd Shahudi, Muhammad Shukri; Muhammad Faudzi, Nuralya Maisarah; Zainal Abidin, Noranisa (2021)
We are making baking boxes from raw ingredients that have been carefully measured, selected and packed to be sold to our customers to start our business. We chose to start up this concept as a business because we see an opportunity to sell a box of baking ingredients that have the potential to grow in the Malaysia market. The box could serve a variety of purposes from being a hobby, learning new cooking techniques or opening a small-scale bakery. We also provide online delivery as well as in-store purchases to increase our geographic segmentation. The price for each box depends on various reasons from the type of product to the number of ingredients. Price per unit for Pie bakebox is RM 26.50, Cake bakebox is RM30.00, Cookies bakebox is RM25.50, Cupcake/Muffin bakebox is RM22.90 and lastly, Pancake bakebox is RM18.00. More, the customer could customize the number of baked goods in the box for an additional cost. The prices for all our products are slightly above average pricing of baked goods in the market. The reasons are to maintain the high quality of baked goods we provide to our customers. Even with the slightly high prices, we believe that our products could increase market share and increase in profit as the year goes by. This business venture will start on 29 October 2020. We will start the venture with a total of eight-person which are general manager, marketing manager, administration manager, financial manager, operating manager and three staff. We chose Selangor to open our store which is located at Savanna Dengkil Lifestyle Retail, Bangi after looking into various aspects. The competitors for our store would be Bakes by Lola, Omma kitchen & bakery, Sweetoothdelight Café & Baking Studio and KetuharBakeri which are located not far from our store. Our competitors have strength and weakness for example strength on a variety of products, provide postage to all over Malaysia and sell various brands while for weakness are did not sell baking ingredients, did not provide premeasured baking ingredients and recipe.